12-Month Clinical Follow-Up of Patients Undergoing Early Invasive Strategy by the Transradial or Transfemoral Approach with Vascular Closure Device - Andrade,Pedro Beraldo de (2017)
Abstract Background: The radial approach reduces the prevalence of vascular complications, major bleeding and mortality when compared to the femoral approach. However, the last still prevails as the preferred approach for the performance of invasive coronary procedures, requiring the adoption of strategies to minimize complications. Objectives: To compare the survival free of major adverse cardiovascular events at 12 months in patients undergoing early intervention strategy by the radial or femoral access with vascular closure device. Methods: Randomized non inferiority trial involving 240 non-ST-segment elevation acute coronary syndrome patients. The survival free of death, myocardial infarction or stroke was estimated by the Kaplan-Meier method and compared using the log rank test. Results: The 30-day rate of vascular complications in the arterial puncture site was 12.5% in the Angio-Seal group and 13.3% in the radial group (p = 1.000). The 12-month incidence of major bleeding or blood transfusion did not differ between groups (2.5% vs. 1.7%, p = 1.000). There was no difference in survival free of major adverse cardiovascular events (90.8% versus 94.2%, p = 0.328). Conclusions: There was no distinction between the techniques in survival free of major adverse cardiovascular events at 12 months of follow-up. Clinical trials with greater statistical power are needed to validate these findings.